Ks. płk Wacław Pyszkowski – Generalny Dziekan Wojska Polskiego 1947-1950 - Łuczak, Piotr (Śląskie Studia Historyczno-Teologiczne, 2023)
Article describes life and activity of father Wacław Pyszkowski, during 3 years of being General Dean of Polish Army. This article was focused to show the complicated personality and difficult lifetimes of father Pyszkowski. Before WWII he was involved in patriotic operations during fight for independence. In thirties he has been engaged in antigovernment actions opposite to marshal Piłsudski. Most time of WWII he spent in Great Britain where he was a chaplain in Polish Army on the West. He came back to Poland in 1946 and instantly he started to work for bureau of General Dean of Polish Army, as a vice dean. In 1947 he became general dean. He was one of the priests who collaborated with communist regime. Because of his position, he has been a kind of icon for the other priests who also have been cooperated with government. He was one of the leaders of organization which concentrated “Patriot Priests”. He stood in the forefront battle with church hierarchy which was focused on problems with jurisdiction. Problem was also in observance and the binding force of the concordat which was signed in 1926. During those three years he has written some articles. These texts might be an interpretation of his own social theology. In his theological thinking he has always shared society by two groups. One group is called Folk, and in this group he placed also Jesus Christ. Second group is connected with possessing, and in that group found church hierarchy. The two groups are separated, and they have different purposes. Right place for modern priest is to be always with the Folk, especially when this Folk has de facto authority.